HUBUNGAN MOTIVASI KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SD KECAMATAN JAWAI SELATAN - Sari, Purnama (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
AbstractThis research is to describe the relationship between principal's motivation and school culture on the performance of elementary school teachers in jawai selatan, Sambas. This study consisted of two independent variables and one dependent variable. They are the principal's motivation (X1) and school culture (X2) as independent variables, and teacher performance (Y)as dependent variable. The subjects of this study are all elementary school teachers. This study uses a quantitative approach with a descriptive correlational design. Data collection techniques used are documentary and questionnaire techniques. The main data collection tool used is a questionnaire (questionnaire) with alternative answers in the form of a Likert scale. Technical analysis or data processing of this study using descriptive statistics and inferential statistics. The results obtained: (1) There is a relationship between the principal's motivation and teacher performance of 25.70%. (2) There is a significant relationship between school culture and an increase in teacher performance of 70.13%. (3) The principal's motivation and school culture have a significant relationship to the performance of teachers in the southern Jawai sub-district with a contribution of 55.70%.Â Keywords: Motivation, School Culture, Performance of teachers